Analisis Perbandingan Kinerja Tools Manajemen Proyek (Trello Vs Jira) Menggunakan Metode Pieces - Anggun Fergina; Siti Zahra Sifa; Taufik Hidayat; Imam Sanjaya; Aulia Kusuma Wardani (Riset Sinergi Indonesia (RISINDO), 2026)
Effective project management highly depends on selecting the appropriate tools to support team productivity. This study focuses on comparing the performance of two popular project management platforms, Trello and Jira, which are widely used by software development teams. The issue addressed in this research concerns the differences in features and levels of flexibility that often make it difficult for organizations to determine the most efficient tool according to their needs. Therefore, this study aims to objectively evaluate the effectiveness of both platforms and provide recommendations for selecting project management tools that best suit organizational requirements. The benefit of this research is to provide information and references for project managers and software development teams in determining the most suitable project management platform. The method used is a comparative analysis based on the PIECES framework (Performance, Information, Economics, Control, Efficiency, and Service) with a quantitative approach through observation and questionnaire distribution to 30 respondents. The collected data were analyzed based on the six PIECES dimensions to measure the performance level of each platform. The results indicate that Trello achieved higher scores in the Performance (4.8), Economics (4.7), and Efficiency (4.6) dimensions, while Jira outperformed Trello in Information (4.9), Control (4.8), and Service (4.6). Overall, Jira obtained a higher average score of 4.35 compared to Trello's 4.16. In conclusion, Jira is more suitable for managing complex projects that require better control and information management, whereas Trello is more appropriate for small- to medium-scale projects that prioritize ease of use and operational efficiency.